An intelligent technique for generating equivalent gyrator circuits using Genetic Algorithm. Issue 11 (November 2015) - Khalil, Nariman A.; Ahmed, Rania F.; Abul seoud, Rania A.; Soliman, Ahmed M.
Abstract: Genetic algorithm (GA) applications in analog design circuits play an important role with promising results. This algorithm is utilized to generate equivalent circuits for the well-known gyrator circuit which is the most commonly used active circuit for the realization of a grounded inductor. The conventional gyrator circuit is realized by the op-amp which has the drawback of frequency limitations. This paper introduces the gyrator-GA Technique. It is an intelligent technique for generating equivalent gyrator circuits utilizing Second Generation Current Conveyor (CCII) as well as Transconductance Amplifier (TA) circuits. The proposed algorithm is based on the pathological representation of the active blocks. As illustrations to demonstrate the systematic realization of gyrator-GA, a fifth-order Butterworth lowpass filter is designed and simulated using PSPICE.